An endogenous growth model of money, banking, and financial repression - Marco Espinosa; Chong K. Yip (Federal Reserve Bank of Atlanta, 1996)
In this paper, we develop an endogenous growth model with financial intermediation to examine the effects of financial repression on growth, inflation, and welfare. By limiting the liquidity provision, binding reserve requirements always suppress economic growth while their effect on inflation is a function, among other things, of the degree of repression. For example, contrary to previous claims, if financial repression is severe enough so that an informal financial sector emerges, liberalization is inflationary. Notwithstanding, liberalization in these cases is always welfare improving. Finally, we characterize the condition that gives rise to a unique optimal level of binding reserve requirements, i.e., the optimal degree of "moderate" financial repression.
Keywords: 330; Financial markets; Money theory